UPLC-MS/MS Analysis of Urinary Free Oligosaccharides for Lysosomal Storage Diseases: Diagnosis and Potential Treatment Monitoring. (4th January 2020) - Huang, Rongrong; Cathey, Sara; Pollard, Laura; Wood, Tim
Abstract: BACKGROUND: The glycoproteinoses are a subgroup of lysosomal storage diseases (LSDs) resulting from impaired degradation of N-linked oligosaccharide side chains of glycoproteins, which are commonly screened by detecting the accumulated free oligosaccharides (FOSs) in urine via thin layer chromatography (TLC). The traditional TLC method suffers from limited analytical sensitivity and specificity and lacks quantification capability. Therefore, we developed an analytically sensitive and relatively specific assay using ultraperformance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) for urinary FOS analysis and validated its use for urine screening of glycoproteinoses and other LSDs. METHODS: Urine volumes equivalent to 30 μg of creatinine were derivatized with butyl-4-aminobenzoate and then purified through a solid-phase extraction cartridge. A 7-min UPLC-MS/MS analysis was performed on a triple quadrupole mass spectrometer using an amide column for separation of derivatized FOS. Urine samples from >100 unaffected controls and 37 patients with various LSDs were studied. RESULTS: Relative quantification was conducted on 7 selected FOSs using a single internal standard, which allowed the identification of patients with 1 of 8 different LSDs: aspartylglucosaminuria, α-fucosidosis, α-mannosidosis, β-mannosidosis, β-galactosidase deficiency, Sandhoff disease, sialidosis, and galactosialidosis. Patients treated with hematopoietic stem cell transplant show decreased FOS responses compared with untreated patients. CONCLUSIONS: This UPLC-MS/MS assay offers a valuable tool for screening of glycoproteinoses and other LSDs, with potential use for future treatment monitoring.